Nurses' knowledge of law at the end of life and implications for practice: A qualitative study. (April 2020) - Willmott, Lindy; White, Ben; Yates, Patsy; Mitchell, Geoffrey; Currow, David C; Gerber, Katrin; Piper, Donella
Background: Some patients do not receive adequate pain and symptom relief at the end of life, causing distress to patients, families and healthcare professionals. It is unclear whether undertreatment of symptoms occurs, in part, because of nurses' concerns about legal and/or disciplinary repercussions if the patient dies after medication is administered. Aim: The aim was to explore nurses' experiences and knowledge of the law relating to the provision of end-of-life pain and symptom relief. Design: Semi-structured interviews with nurses were assessed using a six-stage hybrid thematic analysis technique. Setting/participants: Four face-to-face and 21 telephone interviews were conducted with nurses who routinely prescribed and/or administered pain and symptom relief to patients approaching the end of their lives in Queensland and New South Wales, Australia. Results: While many nurses had no personal experiences with legal or professional repercussions after a patient had died, the fear of hastening death and being held accountable was frequently discussed and regarded as relevant to the provision of inadequate pain and symptom relief. Concerns included potential civil or criminal liability and losing one's job, registration or reputation. Two-thirds of participants believed that pain relief was sometimes withheld because of these legal concerns. Less than half of the interviewed nurses demonstrated knowledge of the doctrine of double effect, the legal protection for health professionals who provide end-of-life pain and symptom relief. Conclusion: Education is urgently required to strengthen nurses' knowledge of the legal protections supporting the provision of appropriate palliative medication, thereby improving their clinical practice with end-of-life patients.